Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andrés; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell death and differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.